Debilitating Research: Scholarship of the Obvious and Epistemic Trauma - Mohamed, Kharnita (African studies (Johannesburg), 2024)
Research on violence can be debilitating and traumatic. Research fields that explore obvious violence that is largely ignored, minimised or erased can induce epistemic effects that may look like failure or procrastination. That there is very little research on or support for researchers who do research on violence lays bare the ontological presuppositions of the ideal researcher. This article explores what it felt like to do research where ontological erasure was normalised, and places pressure on the presuppositions of the ideal researcher amid scholarship on obvious violence. Debilitation can be a response to epistemic gaslighting, epistemic violence and epistemic trauma and indicate affective refusals and ethical tussling. Being brought to a standstill by research on violence can offer critical epistemic insight that requires using and valuing failure as symptomatic of epistemic relations and refusing the hyper-ableist demands of the academy.